Atmospheric Stability Effects on Offshore and Coastal Wind Resource Characteristics in South Korea for Developing Offshore Wind Farms - Geon Hwa Ryu; Young-Gon Kim; Sung Jo Kwak; Man Soo Choi; Moon-Seon Jeong; Chae-Joo Moon (Energies, 2022)
South Korea is surrounded by the sea on three sides. The characteristics of offshore wind resources vary from region to region due to the influence of the distribution of the coastline and differences in roughness length and atmospheric stability between the coast and the sea. In particular, turbulent gusts and low-level wind shear occurring near the hub height of the wind turbine within the atmospheric boundary layer have a significant effect on the load of wind turbines. These severe weather phenomena are closely related to atmospheric stability. Therefore, the objective of this study is to determine differences in wind resource characteristics in the South Korean offshore and coast in relation to variations in atmospheric stability using observation data from the HeMOSU-1 meteorological tower in the West Sea and the Boseong meteorological observation tower on the southern coast. On the southern coast, changes in sea and land breezes are observed throughout diurnal and nocturnal periods, with an atmospheric stability distribution similar to that of land, which is unstable during the day and becomes more stable at night. On the other hand, the stable ratio continues to dominate in the west offshore. In the case of coastal areas, low-level wind shear occasionally occurs near the general wind turbine hub height approximately over 100 m due to the influence of winds from the sea. This study shows that when constructing an offshore wind farm, it is necessary to first analyze the characteristics of local coastal and offshore wind resources for more efficient and safe wind farm construction and operation.